Speech processing for ip networks : - Burke, Dave (John Wiley & Sons, 2007)
Speech Processing for IP Networks brings these technologies together into a single volume, giving the reader a solid technical understanding of the principles of MRCP, how it leverages other protocols and specifications for its operation, and how it is applied in modern IP-based telecommunication networks. Focusing on the MRCPv2 standard developed by the IETF SpeechSC Working Group, this book will also provide an overview of its precursor, MRCPv1.